2011
DOI: 10.1371/journal.pone.0018822
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of Inhibitory Synaptic Inputs and Rebounds in Deep Cerebellar Nuclear Neurons

Abstract: Neuronal function depends on the properties of the synaptic inputs the neuron receive and on its intrinsic responsive properties. However, the conditions for synaptic integration and activation of intrinsic responses may to a large extent depend on the level of background synaptic input. In this respect, the deep cerebellar nuclear (DCN) neurons are of particular interest: they feature a massive background synaptic input and an intrinsic, postinhibitory rebound depolarization with profound effects on the synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
140
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(159 citation statements)
references
References 68 publications
(121 reference statements)
19
140
0
Order By: Relevance
“…Rebound spiking, another intrinsic property of DCN neurons, is regarded as encoding the amplitude of inhibitory synapses in cerebellar circuit and serving to transfer inhibitory signals (Pedroarena, 2010). Interestingly, AHP increases were also seen in rebound spikes from post-weaning rats, which suggests maturation of synaptic inputs especially the inhibitory inputs (Waters et al, 2006) may be required for associative cerebellar learning (Bengtsson et al, 2011; Person and Raman, 2012; Witter et al, 2013). …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Rebound spiking, another intrinsic property of DCN neurons, is regarded as encoding the amplitude of inhibitory synapses in cerebellar circuit and serving to transfer inhibitory signals (Pedroarena, 2010). Interestingly, AHP increases were also seen in rebound spikes from post-weaning rats, which suggests maturation of synaptic inputs especially the inhibitory inputs (Waters et al, 2006) may be required for associative cerebellar learning (Bengtsson et al, 2011; Person and Raman, 2012; Witter et al, 2013). …”
Section: Discussionmentioning
confidence: 96%
“…In addition, there was an increase in AHP amplitude – an index of membrane excitability shown to be important for classical conditioning (Coulter et al, 1989; Schreurs et al, 1998; Wang and Schreurs, 2010) which was accompanied by a prolonged S1S2 interval. Interestingly, an increased AHP amplitude was also observed for the hyperpolarization-elicited rebound spikes, which are modulated by synaptic inputs on DCN especially inputs from Purkinje cells and climbing fibers (Aizenman and Linden, 1999; Bengtsson et al, 2011; Person and Raman, 2012; Zheng and Raman, 2010) and define the accuracy and timing of cerebellar motor performance (Witter et al, 2013). Taken together, these developmental changes represent the maturation of membrane properties of rat DCN neurons and may help explain the enhanced acquisition of conditioned eyeblink responses at this specific period (Freeman, Jr. et al, 1995; Freeman, Jr. and Nicholson, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anesthesia might alter physiological properties of CN neurons. However, recent studies (25,32) have demonstrated that rebound excitation in CN neurons requires the extensive activation of the presynaptic PCs. Thus, a more likely interpretation is that our protocol of illumination leads to poorly synchronized PC discharges and/or fails to recruit enough presynaptic PCs.…”
Section: Discussionmentioning
confidence: 99%
“…These may be especially prominent after climbing fiberinduced synchronous discharge of complex spike firing of a population of Purkinje cells (Hoebeek et al, 2011). To what extent this rebound firing has a functional characteristic is still a matter of debate (Alvina et al, 2008;Bengtsson et al, 2011;Hoebeek et al, 2011). Even less is known on the responses to Purkinje cell activity of the other populations of cerebellar neurons (Uusisaari and De Schutter, 2011;Uusisaari and Knopfel, 2011).…”
Section: Purkinje Cell Axonsmentioning
confidence: 99%